Acro‐osteolysis, keloid like‐lesions, distinctive facial features, and overgrowth: Two newly recognized patients with premature aging syndrome, penttinen type. Issue 7 (29th May 2013) - Zufferey, Flore; Hadj‐Rabia, Smaïl; De Sandre‐Giovannoli, Annachiara; Dufier, Jean‐Louis; Leheup, Bruno; Schweitze, Cyril; Bodemer, Christine; Cormier‐Daire, Valérie; Le Merrer, Martine
Abstract We report on two unrelated patients with a rare progeroid syndrome first described by Penttinen. Patients presented with prematurely aged appearance, delayed dental development, acro‐osteolysis, diffuse keloid‐like lesions, and ocular pterygia. Facial features are progressive but recognizable at birth. Premaxillary and maxillary retraction with pseudo‐prognathism and palpebral malocclusion are characteristic. Thumbs and halluces are broad and spatulated. Linear growth is increased and intellectual functions are preserved. Skin retractions and joint contractures progressively developed during adolescence. Death occurred in the second decade in one of the patient due to restrictive respiratory insufficiency and cachexia. LMNA and ZMPSTE24 sequencing were normal. The molecular basis of the disorder remains unknown. © 2013 Wiley Periodicals, Inc.